Good pictures a history of popular photography - Beil, Kim (Stanford University Press, 2020)
A picture-rich field guide to American photography, from daguerreotype to digital. We are all photographers now, with camera phones in hand and social media accounts at the ready. And we know which pictures we like. But what makes a 'good picture'? And how could anyone think those old styles were actually good? Soft-focus yearbook photos from the'80s are now hopelessly—and happily—outdated, as are the low-angle portraits fashionable in the 1940s or the blank stares of the 1840s. From portraits to products, landscapes to food pics, Good Pictures proves that the history of photography is a history of changing styles. In a series of short, engaging essays, Kim Beil uncovers the origins of fifty photographic trends and investigates their original appeal, their decline, and sometimes their reuse by later generations of photographers. Drawing on a wealth of visual material, from vintage how-to manuals to magazine articles for working photographers, this full-color book illustrates the evolution of trends with hundreds of pictures made by amateurs, artists, and commercial photographers alike. Whether for selfies or sepia tones, the rules for good pictures are always shifting, reflecting new ways of thinking about ourselves and our place in the visual world.